Millennium BCP equity research - one bank, 3 worlds - Sousa, Júlio Santos (2022)
This is one of two parts of an Equity Research on the Portuguese Bank Millennium BCP. In this part, an overview of the banking industry is made, Forecasts for Commission Income are explained and Provisions for FX Loans in Poland were analyzed. The valuation, using a EFCF method was concluded. A multiple analysis was also carried out and possible M&A deals and their returns were explored. The target share price is €0.2020, as of 21/05/2021.